SCIENCE EDUCATION IN THE TECHNOLOGICAL SYSTEM OF VERACRUZ: A GENDER PERSPECTIVE - Villarruel-Fuentes, Manuel (2017)
Since the beginning, science activity has been conceived as a male-gender occupation. Despite the efforts to bring women into scientific research communities, there is still much to be done. In view of the foregoing, a study was conducted with the aim to identify, with a gender-based approach, the types of teaching and learning styles at the technological institutes in the state of Veracruz, Mexico. For that purpose, an instrument with closed-ended and multiple-choice items was applied to assess the teaching models used by teachers of those institutes. This exploratory, descriptive and ex post facto study covered 9 institutes and 396 students (55.8% men and 44.2% women) who were participating in a research project. Results showed that teachers, regardless of their gender, prioritize experiential learning through discovery, following the premises of meaningful learning and constructivism, therefore being necessary to reinforce the learning environments and teaching strategies they use, guiding them towards alternative models, mainly within the Science-Technology-Society approach.